Synergy Analysis of Biomass and Polystyrene Co-Pyrolysis Products Using a Microwave-Assisted - Nazarrudin, Rizal; Chanief Hidayat, Nashrul; Wahyu Ayatullah, Maulana; Akbarsah, Anugrah (FTMD Institut Teknologi Bandung, 2024)
This study aims to synergize pyrolytic oil products obtained through co-pyrolysis of biomass (palm shells) and food packaging waste (polystyrene) with the addition of a mixture of natural zeolite catalysts and CaO using a microwave-assisted. The main raw materials of palm shells and polystyrene are mixed with a ratio of 1:1 plus coconut charcoal as absorber 50% of the total main raw materials, and the catalyst mixture ratio is 1:1. This study used microwaves as a reactor with various power variations, namely 300 watts, 450 watts, 600 watts, and 800 watts. Analysis of pyrolytic oil products in the form of calorific value using a bomb calorimeter and chemical composition using mass spectrometry. The results showed that the optimal power to use was 600 W, with a calorific value (HHV) of pyrolytic-oil of 40.10 MJ/Kg, and a percentage of compound content of 99.19% dominated by aromatic compounds 17.83% and aliphatic 76.93% with high hydrocarbon content.